Technical skill training framework and skill load measurements for the Rugby Union tackle - Hendricks, S.; Till, K.; Oliver, J. L.; Johnston, R. D.; Attwood, M.; Brown, J.; Drake, D.; MacLeod, S.; Mellalieu, S. D.; Treu, P.; Jones, B. (Strength and Conditioning Journal, 2018)
Drawing from skill acquisition and development literature, we present a novel tackle skill training framework. The framework outlines the training purpose (technique proficiency, technique capacity, skill proficiency, and skill capacity), skill workload measurements (available information, task difficulty, rating of perceived challenge, and skill load), as well as the training conditions and coaching style for the tackle in rugby union. Using this framework and skill load measurements, we propose a preseason tackle training plan. This tackle skill framework and skill load measurements serve as potential preventive measures for tackle injury risk while improving players' tackle performance.